Factor Affecting the Utilization of Family Planning Program Services for Women in the Working Area of the Pasie Raya Community Health Center - Melda Andriani; Megawati Megawati; Asriwati Amirah; Lucia Lastiur (Newinera Publisher, 2021)
Family planning to spacing or planning the number and distance of pregnancies using contraception. Data on active family planning participants based on the type of contraception at the Pasie Raya Community Health Center in 2019 was 39.4%, there was no increase in the coverage of active KB participants based on the type of contraception in 2018 of 49.4%. The aim is to find out what are the factors that influence the use of family planning program services for women in the working area of ​​the Pasie Raya Community Health Center. This type of research is a combination research (mixed methods research) combining or combining quantitative methods and qualitative methods with Accidental Sampling sampling techniques on 90 samples and 5 informants. Quantitative data were analyzed using univariate, bivariate and multivariate logistic regression tests. The results of the study showed the influence of knowledge, information sources, culture, family support and support from health workers on the utilization of family planning program services. Based on the multivariate analysis, the support variable for health workers is the dominant variable, while the results of the qualitative analysis on key informants and supporters can be concluded that women have taken advantage of the Kb service program, but most of the women do not understand and understand the benefits that are obtained from the family planning program. The conclusion from the health workers is very important in the utilization of family planning program services. It is recommended that the Health Office conduct more evaluations of family planning services at the Puskesmas. It is necessary to improve the quality of Kb services by including health workers in training.